Thyroid dysfunction may be associated with poor outcomes in patients with COVID-19. (5th February 2021) - Zhang, Yan; Lin, Fengyu; Tu, Wei; Zhang, Jianchu; Choudhry, Abira Afzal; Ahmed, Omair; Cheng, Jun; Cui, Yanhui; Liu, Ben; Dai, Minhui; Chen, Lingli; Han, Duoduo; et al.
Abstract: Background: Coronavirus disease (COVID-19) has resulted in considerable morbidity and mortality worldwide. Thyroid hormones play a key role in modulating metabolism and the immune system. However, the prevalence of thyroid dysfunction (TD) and its association with the prognosis of COVID-19 have not yet been elucidated. In this study, we seek to address this gap and understand the link between TD and COVID-19. Methods: Herein, we enrolled patients who were hospitalized with COVID-19 and had normal or abnormal thyroid function test results at the West Court of Union Hospital in Wuhan, China, between 29 January and February 26, 2020. We carried out follow up examinations until April 26, 2020. Data on clinical features, treatment strategies, and prognosis were collected and analyzed. TD was defined as an abnormal thyroid function test result, including overt thyrotoxicosis, overt hypothyroidism, subclinical hypothyroidism, subclinical hyperthyroidism, and euthyroid sick syndrome. Results: A total of 25 and 46 COVID-19 patients with and without TD, respectively, were included in the study. COVID-19 patients with TD had significantly higher neutrophil counts and higher levels of C-reactive protein, procalcitonin, lactate dehydrogenase, serum creatine kinase, aspartate transaminase, and high-sensitive troponin I and a longer activated partial thromboplastin time but lower lymphocyte, platelet, and eosinophil counts. A longitudinal analysis of serum biomarkers showed that patients with TD presented persistently high levels of biomarkers for inflammatory response and cardiac injury. COVID-19 patients with TD were more likely to develop a critical subtype of the disease. Patients with TD had a significantly higher fatality rate than did those without TD during hospitalization (20% vs 0%, P = 0.002). Patients with TD were more likely to stay in the hospital for more than 28 days than were those without TD (80% vs 56.52%, P = 0.048). Conclusions: Our preliminary findings suggest that TD is associated with poor outcomes in patients with COVID-19. Highlights: Baseline characteristics of the patients with COVID-19. Laboratory and radiological findings on admission. Analysis of disease severity, treatment strategies and prognosis. TD is associated with a higher risk of fatality in patients with COVID-19.